SOCIAL ADAPTATION OF CHILDREN IN KINDERGARTEN OF PRESCHOOL AGE - Dekhkambayeva Zulfia Abubakirovna (Web of Journals Publishing, 2023)
The article discusses the directions of social adaptation of preschool children. Problems related to this, methods of adaptation of children
Keywords: social adaptation, primary school children, preschool educational organization, kindergarten, adaptation problems, adaptation methods and adaptation factors.